Loss of TrkB Signaling Due to Status Epilepticus Induces a proBDNF-Dependent Cell Death - Montroull, Laura Ester; Danelon, Víctor; Cragnolini, Andrea Beatriz; Mascó, Daniel Hugo (Frontiers in Cellular Neuroscience, 2019)
Neurotrophins (NT) are secretory proteins that bind to target receptors and influence many cellular functions, such as cell survival and cell death in neurons. The mammalian neurotrophin Brain-Derived Neurotrophic Factor (matBDNF) is the C-terminal mature form released by cleavage from the proBDNF precursor. The binding of matBDNF to the tyrosine kinase receptor TrkB activates different signaling cascades and leads to neuron survival and plasticity, while the interaction of proBDNF with the p75NTR /sortilin receptor complex has been highly involved in apoptosis. Many studies have demonstrated that prolonged seizures such as Status Epilepticus (SE) induce changes in the expression of NT, pro-NT, and their receptors. We have previously described that the blockage of both matBDNF and proBDNF signaling reduces neuronal death after SE in vivo (Unsain et al., 2008). We used an in vitro model as well as an in vivo model of SE to determine the specific role of TrkB and proBDNF signaling during neuronal cell death. We found that the matBDNF sequestering molecule TrkB-Fc induced an increase in neuronal death in both models of SE, and it also prevented a decrease in TrkB levels. Moreover, SE triggered the interaction between proBDNF and p75NTR, which was not altered by sequestering matBDNF. The intra-hippocampal administration of TrkB-Fc, concomitantly with an antibody against proBDNF, prevented neuronal degeneration. In addition, we demonstrated that proBDNF binding to p75NTR lead to neuronal death only when matBDNF signaling is impaired through TrkB. Our results indicated that both the mature and the precursor forms of BDNF may have opposite effects depending on the scenario in which they function and the signaling pathways they activate.